Determination of HER2/NEU gene amplification and protein overexpression ib bladder transitional cell carcinoma - Atış, Gökhan; Arısan, Serdar; Ayhan, Dalkılınç (İstanbul Kültür Üniversitesi, 2007)
HER2/neu 185 kDa is a transmembrane receptor tyrosine kinase being a part of epidermal growth factor receptor family. Especially overexpression was shown in breast cancer and treatment procedures targeting this protein are in clinical use. The aim of this study is to show the overexpression of HER2/neu in bladder TCC patients by using immunohistochemical methods. 46 TCC and 15 healthy bladder tissues as a control group were used in the study. Deparafinized tumor specimens were marked by using monoclonal antihuman HER2 protein antibody and the protein was shown by using peroxidase secondary antibody. Non-staining or membrane staining less than 10% were classified as 0, while membrane staining partly more than 10% were 1, poor complete membrane staining or moderate staining more than 10% were 2 and complete membrane strongly staining were classified as 3. Classification 2 and 3 were evaluated as over staining of HER2/neu. Overexpression of HER2/Neu protein were shown in 12/46 (24.5%) of TCC specimens. Overexpression of HER2/neu were detected in 2 (12.5%) of Grade 1, 1 (16.6%) of Grade 2 and 12 (50%) of Grade 3 patients. Overexpression of HER2/Neu protein were positive in 5 (17.8%) of 28 superficial (Ta-T1) tumor specimens and 7 (38.8%) of 18 invasive (T2-T3) tumor specimens. Overexpression of HER2/neu in Grade III tumors were statistically significant when compared with Grade I and Grade II (p=0.012). Overexpression of HER2/neu detected in bladder TCC will be used in clinical setting as a treatment option targeting this protein as in the breast cancer in the future.
Keywords: bladder carcinoma; HER2/neu; protein overexpression; trastuzumab; immunohistochemistry; mesane karsinomu; immünhistokimya; protein overekspresyonu